Cyclanoline Reverses Cisplatin Resistance in Bladder Cancer Cells by Inhibiting the JAK2/STAT3 Pathway - Li, Linjin; Li, Chengpeng; Miao, Feilong; Chen, Wu; Kong, Xianghui; Ye, Ruxian; Wang, Feng (Anti-Cancer Agents in Medicinal Chemistry, 2024)
Background Cisplatin is a key therapeutic agent for bladder cancer, yet the emergence of cisplatin resistance presents a significant clinical challenge. Objective This study aims to investigate the potential and mechanisms of cyclanoline (Cyc) in overcoming cisplatin resistance. Methods Cisplatin-resistant T24 and BIU-87 cell models (T24/DR and BIU-87/DR) were established by increasing gradual concentration. Western Blot (WB) assessed the phosphorylation of STAT3, JAK2, and JAK3. T24/DR and BIU-87/DR cell lines were treated with selective STAT3 phosphorylation modulators, and cell viability was evaluated by CCK-8. Cells were subjected to cisplatin, Cyc, or their combination. Immunofluorescence (IHC) examined p-STAT3 expression. Protein and mRNA levels of apoptosis-related and cell cycle-related factors were measured. Changes in proliferation, invasion, migration, apoptosis, and cell cycle were monitored. In vivo, subcutaneous tumor transplantation models in nude mice were established, assessing tumor volume and weight. Changes in bladder cancer tissues were observed through HE staining, and the p-STAT3 was assessed via WB and IHC. Results Cisplatin-resistant cell lines were successfully established, demonstrating increased phosphorylation of STAT3, JAK2, and JAK3. Cisplatin or Cyc treatment decreased p-STAT3, inhibited invasion and migration, and induced apoptosis and cell cycle arrest in the G0/G1 phase in vitro. In vivo, tumor growth was significantly suppressed, with extensive tumor cell death. IHC and WB consistently showed a substantial downregulation of STAT3 phosphorylation. These changes were more pronounced when cisplatin and Cyc were administered in combination. Conclusion Cyc reverses cisplatin resistance via JAK/STAT3 inhibition in bladder cancer, offering a potential clinical strategy to enhance cisplatin efficacy in treating bladder cancer.
Keywords: Bladder cancer